Influence of Natural Heritage on Agro-Tourism Development in Nandi County, Kenya - Sawe, J. B.; Korir, J. C.; Burugu, R. W. (Africa Environmental Review Journal, 2020)
This paper determined the influence of natural heritage on agro-tourism development in Nandi County. Predicaments in the agricultural sector form negative attitudes of farmers regarding agriculture that creates a gap for additional sources of income using existing agricultural land and occupation. With existing problems such as low demand and low prices for farm produce, linkages between agriculture and tourism provide the basis for new solutions in Kenya. Explanatory research design was adopted. The target population was 357,461 farmers from Aldai, Tinderet and Nandi-Hills sub-counties with 384 forming the sample size. Three out of six sub-counties that had evidence of agrotourism development were purposively selected and clustered into wards while systematic random sampling was used to identify the farmers from a list provided by agricultural extension officers. Data was collected using structured questionnaires. Cronbach’s Alpha tested reliability at 0.719. Exploratory factor analysis established underlying factor structure of natural heritage. Bivariate analysis tested the hypothesis while qualitative data utilized thematic analysis. The hypothesis negating the influence of natural heritage (β=0.618, p<0.05) on agro tourism development was not supported. The model explained 40.1% (R2=0.401) of the variance in agro tourism development while factor analysis results extracted seven components that explain natural heritage. Interviews revealed the existence of underutilized natural resources such as rivers, hills and rocks in Nandi County. The study concluded that natural heritage components such as serenity, ecosystem, regular practice, forests, riparian areas, landscapes and indigenous food influence agro tourism development positively. Based on the results, Nandi County government should package and utilize its natural heritage to enhance agro tourism development which is it its nascent stage in order to complement agriculture and provide an alternative source of income to farmers.